Subfossil oribatid mite communities indicate Holocene permafrost dynamics in Canadian mires - Inkeri Markkula; Peter Kuhry (WILEY, 2022)
Permafrost thaw in peatlands is one of the most widespread and worrying consequences of climate warming in the sub-Arctic area. To predict future climate feedbacks, it is important to study the history of permafrost aggradation and thaw. Plant macrofossil analysis with radiocarbon dating has been widely used in detecting past permafrost dynamics in peatlands, however, due to a lack of permafrost-specific plant indicator species, determining the exact timing of permafrost aggradation remains a challenge. In this study, we investigated if oribatid mites can be used to determine Holocene permafrost aggradation and degradation in Canadian mires. Based on analyses of subfossil oribatid mite assemblages of Holocene peat profiles from two mires in the Hudson Bay Lowlands area, our results suggest that two species, Carabodes labyrinthicus and Neoribates aurantiacus, are useful bioindicators, which can be used in palaeoecological studies determining permafrost histories. Moreover, our results show that subfossil oribatid mite remains can reveal periods of permafrost, which cannot be determined with certainty based on plant macrofossils alone.